Why humans might help strangers - Raihani, Nichola J.; Bshary, Redouan (Frontiers in Behavioral Neuroscience, 2015)
Humans regularly help strangers, even when interactions are apparently unobserved and unlikely to be repeated. Such situations have been simulated in the laboratory using anonymous one-shot games (e.g., prisoner’s dilemma) where the payoff matrices used make helping biologically altruistic. As in real-life, participants often cooperate in the lab in these one-shot games with non-relatives, despite that fact that helping is under negative selection under these circumstances. Two broad explanations for such behavior prevail. The “big mistake” or “mismatch” theorists argue that behavior is constrained by psychological mechanisms that evolved predominantly in the context of repeated interactions with known individuals. In contrast, the cultural group selection theorists posit that humans have been selected to cooperate in anonymous one-shot interactions due to strong between-group competition, which creates interdependence among in-group members. We present these two hypotheses before discussing alternative routes by which humans could increase their direct fitness by cooperating with strangers under natural conditions. In doing so, we explain why the standard lab games do not capture real-life in various important aspects. First, asymmetries in the cost of perceptual errors regarding the context of the interaction (one-shot vs. repeated; anonymous vs. public) might have selected for strategies that minimize the chance of making costly behavioral errors. Second, helping strangers might be a successful strategy for identifying other cooperative individuals in the population, where partner choice can turn strangers into interaction partners. Third, in contrast to the assumptions of the prisoner’s dilemma model, it is possible that benefits of cooperation follow a non-linear function of investment. Non-linear benefits result in negative frequency dependence even in one-shot games. Finally, in many real-world situations individuals are able to parcel investments such that a one-shot interaction is turned into a repeated game of many decisions.